A QUALITATIVE ANALYSIS OF STAKEHOLDERS’ VIEWS ABOUT FEMALE CHILD DOMESTIC LABORER’S EDUCATION - Khalid, Sana; Tahira Jabeen (Journal of Arts & Social Sciences, 2025)
AbstractEducation is the fundamental right of every child but domestic child laborers are deprived of this right due to multiple socio-economic and cultural factors. In South Asia, particularly in Pakistan, female children are associated with domestic labor. In this study, female child domestic laborers, their parents and employers are the main stakeholders. Based on this study, the current article aims to analyze the views of female child domestic laborers, their parents and employers about female children’s education. Qualitative methodology was used, employing purposive sampling from different areas of Lahore. Data were collected through in-depth interviews and were analyzed through thematic analysis. Employers and female child domestic laborers have positive views about female education. However, their fathers’ views were revolving around gender discrimination and societal stereotypes related to female role. Thus, study recommends to change the patriarchal mindset of society through adult education.